Removal of Pb2+ from Aqueous Solutions by Rice Hull Adsorbent Modified with Citric Acid Anhydride - Li1, Daiqi; Li1, Jianqiang; Pan2, Qingshan (Asian Journal of Chemistry, 2014)
Rice hull was chemically modified by reacting with citric acid anhydride after microwave pretreatment to prepare carboxylate functionalized rice hull adsorbent for removal of Pb2+ from aqueous solutions. The preparing conditions were optimized in this study. And the effects of carboxylate functionalized rice hull dosage, pH, contact time and initial Pb2+ concentration in aqueous solutions on the removal efficiency of Pb2+ from aqueous solutions was studied. The results indicated that when the initial Pb2+ concentration was 100 mg/L. The adsorption capacity of carboxylate functionalized rice hull was high effective with the carboxylate functionalized rice hull dose was 8 g/L, pH was 4.5 and the contact time was 100 min at room temperature. The equilibrium adsorption capacity of carboxylate functionalized rice hull was 11.45 mg/g and the removal rate of Pb2+ was 91.60 %. All the results indicated that the carboxylate functionalized rice hull was a effective adsorbent for removal of Pb2+ form aqueous solutions.